1998
DOI: 10.1302/0301-620x.80b6.9277
|View full text |Cite
|
Sign up to set email alerts
|

Genotype phenotype correlation in achondroplasia and hypochondroplasia

Abstract: Recent studies of the fibroblast growth factor receptor 3 (FGFR3) gene have established that achondroplasia and hypochondroplasia are allelic disorders of different mutations. To determine whether the genotype could be distinguished on the basis of the phenotype, we analysed height, arm span, and skeletal radiographs from 23 patients with achondroplasia and the G380R mutation of FGFR3 and eight with hypochondroplasia and the N540K mutation. Both conditions share the classical pathological features of micromeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The abnormalities seen in HCH are less severe overall than those seen in ACH and HCH patients have less dysmorphic facial features (Matsui et al. 1998). Most cases can be readily distinguished clinically and radiographically.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormalities seen in HCH are less severe overall than those seen in ACH and HCH patients have less dysmorphic facial features (Matsui et al. 1998). Most cases can be readily distinguished clinically and radiographically.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HCP, the skeletal features are less severe than in patients with ACP (1,2). Therefore, the diagnosis of HCP is often difficult, and some affected patients may be evaluated as idiopathic short stature.…”
Section: Discussionmentioning
confidence: 92%
“…In patients with N540K mutations, adult height ranges from 138 cm to 155 cm in men and from 128 cm to 145 cm in women (13,14). The use of recombinant growth hormone (rGH) therapy for HCP has been evaluated by several centers in trials (2,14,15,16,17,18). In most of these trials, a statistically significant increase in predicted growth rate was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other less frequent mutations are also identified in FGFR3 but are mainly associated with hypochondroplasia and thanatophoric dysplasia type I and II [19]. Therefore, in comparison to other genetic diseases, ACH is a genetically and phenotypically homogenous disorder where very few rather than hundreds of mutations are responsible [20, 21]. In this study a non-consanguineous Pakistani family involving two affected generations, was clinically and genetically characterized for skeletal dysplasia.…”
Section: Introductionmentioning
confidence: 99%